2019
DOI: 10.1371/journal.pone.0209438
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative predation in the social amoebae Dictyostelium discoideum

Abstract: The eukaryotic amoeba Dictyostelium discoideum is commonly used to study sociality. The amoebae cooperate during development, exhibiting altruism, cheating, and kin-discrimination, but growth while preying on bacteria has been considered asocial. Here we show that Dictyostelium are cooperative predators. Using mutants that grow poorly on Gram-negative bacteria but grow well on Gram-positive bacteria, we show that growth depends on cell-density and on prey type. We also found synergy, by showing that pairwise m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…For example, previous approaches to identify mutants that show growth defects have relied on laborious qualitative analysis of large numbers of mutant clones [ 52 ]. Interestingly, many of these are rescued by helper effects in mixed growth with wild-type cells [ 61 ]. The high throughput nature of REMI-seq, together with the fact that the pooled REMI-seq approach is refractive to identifying such mutants, likely explains why a different spectrum of mutants was identified.…”
Section: Discussionmentioning
confidence: 99%
“…For example, previous approaches to identify mutants that show growth defects have relied on laborious qualitative analysis of large numbers of mutant clones [ 52 ]. Interestingly, many of these are rescued by helper effects in mixed growth with wild-type cells [ 61 ]. The high throughput nature of REMI-seq, together with the fact that the pooled REMI-seq approach is refractive to identifying such mutants, likely explains why a different spectrum of mutants was identified.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the myxobacteria appear to differ from amoebae in the degree to which germinating spores and vegetative cells continue to interact and to cooperate. Whereas amoebae may live comparatively solitary lives except when they undergo aggregative development (Rubin et al 2019), the myxobacteria remain social throughout their life cycle. For such systems that cooperate extensively during growth, aggregation may have density benefits that extend beyond the formation, survival and dispersal of spores (Ramsey and Dworkin 1968).…”
Section: Life After Aggregationmentioning
confidence: 99%
“…A recent study suggests that vegetative growth in D. discoideum while preying on bacteria might not be asocial, but instead may involve cooperative predation (Rubin et al, 2019).They found that D. discoideum growth is positively correlated with amoeba density, and mutants that grow poorly on live bacteria can be rescued by the presence of wild-type amoebas and synergistic mutants. They suggest this is due to the secretion of diffusible factors by wild-type cells that facilitates mutant growth, though the molecule mediating such an interaction has not yet been identified.…”
Section: Cooperative Predationmentioning
confidence: 99%